2023
DOI: 10.1177/20965311231179490
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Assisted Reading Instruction for English Language Learners: A Methodological Review

Abstract: Purpose By methodologically reviewing the literature on Technology-Assisted Reading Instruction (TARI) for English Language Learners (ELLs) in K-12 settings, this study aims to advance the knowledge of TARI research and guide future research directions. Design/Approach/Methods This study examines 32 peer-reviewed journal articles published between 2000 and 2020. Each article was analyzed for research objectives, reading skills, learner demographics and contexts, theoretical frameworks, research designs, and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the first paper, "Technology Assisted Reading Instruction for English Learners: A Methodological Review," Zuo and Ives (2023) share a review of 32 peer-reviewed articles published over the past two decades on technology-assisted reading instruction (TARI) for English language learners (ELLs). Their review demonstrates the benefits of TARI for ELL students, as this approach provides scaffolding for students' reading performance, increases their reading motivation, and offers opportunities for collaborative learning.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the first paper, "Technology Assisted Reading Instruction for English Learners: A Methodological Review," Zuo and Ives (2023) share a review of 32 peer-reviewed articles published over the past two decades on technology-assisted reading instruction (TARI) for English language learners (ELLs). Their review demonstrates the benefits of TARI for ELL students, as this approach provides scaffolding for students' reading performance, increases their reading motivation, and offers opportunities for collaborative learning.…”
mentioning
confidence: 99%
“…For example, Kim, Borowiec, et al's (2023) study on EdTech leaders addresses the gap in research on industry partners, but more work is needed. Zuo and Ives (2023) found that most research on TARIs has been conducted on elementary school students, whereas limited research has been…”
mentioning
confidence: 99%
See 3 more Smart Citations